Optimization of Village Government Policy in Strengthening Islamic Education (Case Study of Japan Village, Tegalrejo District) - Suyatno, Suyatno; Irfan, Agus (Universitas Islam Sultan Agung, 2025)
The village government has been given the authority to participate in community empowerment efforts in the field of Education. However,in the educational process, there are still obstacles related to infrastructure. Settlement of these obstacles, still rely on self-help community. The implementation of village government policies as referred to in Law Number 6 of 2014 and regulation of the Minister of Home Affairs of the Republic of Indonesia number 84 of 2015 Article 26 paragraph (2) varies and there are still some that are not optimal. This study aims to determine the optimization of village government policies in efforts to strengthen education. The study was conducted in the village of Japan with a qualitative approach. Subjects were determined using the purposive sampling method. Data collection by observation, interview, and documentation, then analyzed through data reduction, data presentation, and conclusion. The results showed that the form of Village policy in the field of education can be in the form of incentives for educators, operational assistance and infrastructure. The Village policy process has gone through the stages of problem identification, agenda preparation, drafting, ratification, implementation and Policy Evaluation. Village policies in the field of Education have an impact on increasing the spirit of teaching educators, the spirit of learning of learners, and increasing public awareness of the importance of Education. In conclusion, optimizing village policies in the field of education in the form of infrastructure, through a good process can increase the spirit of learning and teaching.